FRI0637-HPR Measurement of Fatigue in RA: The Construct Validity of a Multidimensional Computerized Adaptive Test. (9th June 2015) - Nikolaus, S.; Bode, C.; Taal, E.; Vonkeman, H.; Glas, C.; van de Laar, M.
Abstract : Background: Computerized adaptive testing (CAT) provides the possibility to measure patient reported outcomes precisely at an individual level. Items are selected from a large item pool, based on the previous answer of a patient. Multidimensional CAT has the further advantage that simultaneous measurement of multiple dimensions increases the efficiency of the adaptive item selection procedure. Thereby comprehensive measurement across different aspects of fatigue becomes possible. Objectives: We developed a multidimensional CAT for fatigue in RA. The CAT Fatigue RA was constructed based on a previously calibrated item bank and contains 196 items and three dimensions: severity, impact and variability of fatigue. Aim of this study was the construct validation of the CAT Fatigue RA. Methods: The CAT was administered to 166 patients with RA. They also completed a traditional, multidimensional fatigue questionnaire (Bristol Rheumatoid Arthritis Fatigue Multi-Dimensional Questionnaire; BRAF-MDQ) and the 36-item short-form (SF-36) in order to examine the CAT's construct validity. Furthermore, comprehensive use of the item bank, measurement precision and score distribution were investigated. Results: Construct validity was supported for the dimensions "severity" and "impact". Respectively 87% of the correlations with the well-established questionnaires were as expected. For the dimension "variability", 53% of the hypothesised relations were found. Most items (89%) have been selected for the CAT administrations between one and 137 times. Measurement precision was excellent for the "severity" and "impact" dimensions with more than 90% of the CAT administrations having a standard error below 0.32. On the "variability" dimension 90% of the standard errors lay below 0.44 what still indicates a good reliability. No floor- or ceiling effects were found on the three dimensions. Conclusions: The CAT Fatigue RA showed good construct validity and excellent measurement precision on the dimensions "severity" and "impact". The dimension "variability" had less ideal measurement characteristics, pointing to the need to recalibrate the CAT item bank with a two-dimensional model. Finally, the CAT Fatigue RA can be used in daily clinical practice and for research purposes. References: Nikolaus S, Bode C, Taal E, Vonkeman H, Glas CAW, van de Laar MAFJ. Acceptance of new technology: a usability test of a computerized adaptive test for fatigue in rheumatoid arthritis. Journal of Medical Internet Research Human Factors 2014; 1(1):e4. doi 10.2196/humanfactors.3424. Nikolaus S, Bode C, Taal E, Vonkeman H, Glas CAW, van de Laar, MAFJ (in press).Working mechanism of a multidimensional computerized adaptive test for fatigue in rheumatoid arthritis. Health and Quality of Life Outcomes. Disclosure of Interest: None declared